Impact of biofertilizers, vermicompost and Trichoderma on growth and yield in strawberry (Fragaria × ananassa) cv. Sweet Charlie - KUMAR, ANIL; GAUTAM, DHARMENDRA KUMAR; BEER, KARMA; GUPTA, ANAND K; GUPTA, ALOK; SINGH, ASHUTOSH K; SINGH, VIVEK K (The Indian Journal of Agricultural Sciences, 2020)
Strawberry (Fragaria × ananassa Duch.), a popular fruit which is widely cultivated in temperate as well as subtropical climate. It has a unique place among cultivated berry fruits. The present investigation was carried out at the experimental field of Department of Horticulture, Sam Higginbottom University of Agriculture, Technology and Sciences (SHUATS), Prayagraj, India. Growth and yield parameters were recorded in experiment and it was found that maximum plant height, plant spread, number of leaves and leaf area were observed with T11 (5 kg ha-1 Trichoderma + 2.5 t ha-1 Vermicompost + 7 kg ha-1 Azotobacter + 6 kg ha-1 PSB + 20 kg ha-1 VAM) followed by T5 (5 kg ha-1 Trichoderma + 2.5 t ha-1 Vermicompost + 7 kg ha-1 Azotobacter), whereas minimum was reported in control (T0). Plant height ranged from 12.15 cm and 16.68 cm while plant spread ranged from 12.15 cm to 16.68 cm. Number of leaves per plant ranged from 11.58 to 15.76. The leaf area varied from 64.56 cm2 to 74.64 cm2. Maximum yield per plant was recorded in plants treated with T11 (5 kg ha-1 Trichoderma + 2.5 t ha-1 Vermicompost +7 kg ha-1 Azotobacter + 6 kg ha-1 PSB + 12 kg ha-1 VAM). Fruit yield per plant varied from 53.00 g to 111.08 g in different treatment combinations.